Long-term Evolution of Warps in Debris Disks—Application to the Gyr-old System HD 202628 - Madison T. Brady; Virginie Faramaz-Gorka; Geoffrey Bryden; Steve Ertel (The Astrophysical Journal, 2023)
We present the results of N -body simulations meant to reproduce the long-term effects of mutually inclined exoplanets on debris disks, using the HD 202628 system as a proxy. HD 202628 is a Gyr-old solar-type star that possesses a directly observable, narrow debris ring with a clearly defined inner edge and nonzero eccentricity, hinting at the existence of a sculpting exoplanet. The eccentric nature of the disk leads us to examine the effect on it over Gyr timescales from an eccentric and inclined planet, placed on its orbit through scattering processes. We find that, in systems with dynamical timescales akin to that of HD 202628, a planetary companion is capable of completely tilting the debris disk. This tilt is preserved over the Gyr age of the system. Simulated observations of our models show that an exoplanet around HD 202628 with an inclination misalignment ≳10° would cause the disk to be observably diffuse and broad, which is inconsistent with Atacama Large Millimeter Array (ALMA) observations. With these observations, we conclude that, if there is an exoplanet shaping this disk, it likely had a mutual inclination of less than 5° with the primordial disk. The conclusions of this work can be applied either to debris disks appearing as narrow rings (e.g., Fomalhaut and HR 4796) or to disks that are vertically thick at ALMA wavelengths (e.g., HD 110058).